An Analysis of The “Clean Friday” Program in Shaping Environmentally Conscious Character Among Elementary School Students - Siti Reynalda Pebrianti; Rajji Koswara Adiredja; Abdul Hakim (Universitas Muhammadiyah Lamongan, 2026)
Character education plays an important role in life, one of which is in shaping environmentally conscious characters. However, in practice, deviations are still found, such as littering behavior. This study aims to analyze the implementation of the Clean Friday program in shaping students' environmentally conscious characters. The study used a qualitative approach with a case study method. The research instruments included observation, interviews, documentation, and questionnaires. The research subjects were the principal, two fifth-grade teachers, and fifth-grade students at SDN 1 Balewangi. The results showed that Clean Friday was carried out routinely and involved the entire school community. This activity fostered the habit of disposing of waste in its place, caring for plants, and maintaining environmental cleanliness. Based on the questionnaire results, 98% of students strongly agreed that this activity shaped environmentally conscious characters. In conclusion, the Clean Friday program is effective in shaping environmentally conscious characters through positive and consistent habits.